THEOLOGIA SISTEMATIKA BAGI SPIRITUALITAS KAUM MUDA DI ERA DISRUPSI: Kata Kunci: Theologia Sistematika, Spiritualitas, Kaum Muda, Era Disrupsi - Shendy Lumintang (Sekolah Tinggi Teologi Excelsius, 2024)
This research aims to describe the importance of systematic theology in shaping and strengthening the spirituality of young people amidst the challenges of the disruption era. of young people amidst the challenges of the disruption era. This research uses a qualitative approach with a content analysis research method. Through this research, it was found that systematic theology is a pastoral and teaching guideline for the church. In addition, systematic theology is the foundation of thinking that influences the spirituality of young people in the era of disruption. The results of the study are expected to make a significant contribution to the development of a more effective and relevant spirituality development program for the younger generation in churches and Christian educational institutions.